Expanding collaborative care: integrating the role of dietitians and nutrition interventions in services for people with mental illness. (February 2018) - Teasdale, Scott B; Latimer, Geogina; Byron, Annette; Schuldt, Vanessa; Pizzinga, Josephine; Plain, Janice; Buttenshaw, Kerryn; Forsyth, Adrienne; Parker, Elizabeth; Soh, Nerissa
Objective: This article aims to draw mental health clinicians' attention to the connections between nutrition and mental health, and the roles that Accredited Practising Dietitians play in improving mental and physical health through dietary change. Methods: Selective narrative review. Results: Unhealthy dietary practices are common in high prevalence and severe mental illness. Epidemiological evidence demonstrates that nutrients and dietary patterns impact on mental health. In addition, poor physical health is well documented in people with mental illness and the greatest contributor to the mortality gap. Dietary intervention studies demonstrate improved mental and physical health outcomes. Accredited Practising Dietitians translate nutrition science into practical advice to improve the nutritional status of patients with mental illness, and prevent and manage comorbidities in a variety of care settings. Conclusions: Medical Nutrition Therapy offers opportunities to improve the physical and mental health of people living with mental illness.